Light and Temperature Shape the Phenylpropanoid Profile of Azolla filiculoides Fronds - Costarelli, Alma; Cannavò, Sara; Cerri, Martina; Pellegrino, Roberto Maria; Reale, Lara; Paolocci, Francesco; Pasqualini, Stefania (Frontiers in Plant Science, 2021)
Azolla is a genus of floating freshwater ferns. By their high growth and N2 fixation rates, Azolla species have been exploited for centuries by populations of South-east Asia as biofertilizers in rice paddies. The use of Azolla species as sustainable plant material for as diverse applications as feeding, biofuel production, or bioremediation has encountered a growing interest over the last years. However, the high levels of feed deterrent flavonoids in their fronds have discouraged using these ferns as a sustainable protein source for animal consumption. Additionally, information on how and to what extent environmental determinants affect the accumulation of secondary metabolites in these organisms remain poorly understoodscanty and fragmented. Moving from these considerations, here we investigated by an untargeted metabolomic approach the profiles of phenylpropanoid compounds in the fronds of Azolla filiculoides sampled under control and pigment-inducing stressful conditions. In parallel, we assayed the expression of essential structural genes of the phenylpropanoid pathway by quantitative RT-PCR. The present study provides novel information concerning A. filiculoides phenylpropanoid compounds and their temporal profiling in response to environmental stimuli. In particular, we show that besides the already known 3-deoxyanthocyanidins, anthocyanidins, and proanthocyanidins, this fern can accumulate additional secondary metabolites of outstanding importance as chemoattractants, defense compounds, reactive oxygen species (ROS) scavengers but also crucial as dietary components for humans as dehydrochalcones, stilbenes, isoflavones, and phlobaphenes. The present study's findings open to future research to unveil the interplay between genetic and environmental determinants underlying the elicitation of these secondary metabolites in ferns and exploit these organisms as sustainable sources of beneficial metabolites for human health.